Parameters of disavowal : colonial representation in South Korean cinema - An, Jinsoo, 1968- (Global Korea, 2018)
"The colonial experience of the twentieth century from 1910 to 1945 shaped the culture and identity of Korea, yet the manner in which South Korean postcolonial cinema depicts this troubling past has not received sufficient scholarly attention. Parameters of Disavowal seeks to break this hiatus. It approaches the subject of the colonial past in South Korean cinema as a particular kind of postcolonial knowledge production that responds to the repercussions of Cold War geopolitics while also subscribing to the precept of anticolonial nationalism. It advances beyond manifest readings of anticolonial messages by examining how postcolonial cinema not only posits, but also constructs Korean national history through disavowals and elisions of the very past they wish to represent. In particular, this book focuses on how South Korean films have created ways of seeing and imagining the colonial past by privileging certain Korean sites as spaces generating unique meanings and values contrary to the assumed total domination of the colonial power. These films thereby inscribe colonial power within parameters of disavowal, ultimately rendering it delimited, incomplete, and flawed. This unique cinematic mode of visualization, the author argues, has shaped historical thinking about Korea's colonial past and demands further investigation of the relationship between politics and aesthetics in cinema"--Provided by publisher